Probabilidade de financiamento por cartões de crédito híbridos - Ito, Marcos Kenji (2011)
This research aims to identify a statistical model of propensity to revolve through store credit card, in order to maximize the credit appliance and optimize marketing efforts. The descriptive study aims to generate insights for understanding the expansion of consumer credit, in a context of lack of financing options and limitation in distribution channel. There will be a quantitative approach in the customer data base of a financial institution and through the study of socio demographic and transactional it pretends to establish a mathematical model followed by a validation of their predictive ability.